Using Quality Statistical Tools in Measuring Quality Properties of Hot Mix Asphaltic Concrete Product for Road Pavement Projects in Baghdad - Ismail Abdul-Wahab, Bevian (Anbar Journal of Engineering Science, 2010)
Using statistical tools of quality help in identifying the daily production problems.Collecting data will enable the management to diagnose problems affecting the work and correcting the defects in the products and reduce its percentage; such defects cost the organization too much and influence its profits. Histograms were used in presenting the collected data from Amanat Baghdad. The data related to asphaltic concrete produced by its plants . Control charts were used to evaluate these tests. The research indicates differences in the results of mechanical analysis tests also in the asphalt percentage in the asphaltic concrete samples and air voids ratio as in Marshall samples. The results indicated that management of plants has no benefits gained from results tests carried out by the quality control department which indicate and diagnose the variances of the product and recommend the required corrections.